The impact of mobile applications for English Learning : The employability of UABC graduates in the northern border of Baja California, México - Montaño-Rodriguez, María del Socorro; Guadalupe Toledo-Sarracino, David; Samperio-Sanchez, Nahum; López Gaspar, Icela (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
This study aims to analyze the relationship that exists between learning English, employers and the ways in which the teaching of English and language learning is being addressed in the state of Baja California. This research focused on meeting the following objectives: 1. Identify the main professional skils required by the business sector in Baja California from its prospective employees in terms of hiring and job advancement. 2. Analyze the type of communication skills required by the business sector in terms of English proficiency of its graduates in communicative, written and oral competence and the new forms of learning that are available through technology.